No Difference in Behavioral and Self-Reported Outcomes for Simultaneous and Sequential Bilateral Cochlear Implantation: Evidence From a Multicenter Randomized Controlled Trial - Kraaijenga, Véronique J. C.; Ramakers, Geerte G. J.; Smulders, Yvette E.; van Zon, Alice; Free, Rolien H.; Frijns, Johan H. M.; Huinck, Wendy J.; Stokroos, Robert J.; Grolman, Wilko (Frontiers in Neuroscience, 2019)
OBJECTIVE: The primary aim of this study was to longitudinally compare the behavioral and self-reported outcomes of simultaneous bilateral cochlear implantation (simBiCI) and sequential BiCI (seqBiCI) in adults with severe-to-profound postlingual sensorineural hearing loss. DESIGN: This study is a multicenter randomized controlled trial with a 4-year follow-up period after the first moment of implantation. Participants were allocated by randomization to receive bilateral cochlear implants (CIs) either, simultaneously (simBiCI group) or sequentially with an inter-implant interval of 2 years (UCI/seqBiCI group). All sequential patients where encouraged to use their hearing aid on the non-implanted ear over of the first two years. Patients were followed-up on an annual basis. Behavioral outcome measures encompassed speech perception in noise from a source in front, speech intelligibility-in-noise from spatially separated sources, localization and speech perception in quiet. Self-reported outcome measures encompassed questionnaires on quality of life, quality of hearing and tinnitus. RESULTS: Nineteen participants were randomly allocated to the simBiCI group and 19 participants to the UCI/seqBiCI group. Three participants in the UCI/seqBiCI group decided not to proceed with their second implantation and were therefore unavailable for follow-up. Both study groups performed equally well on speech perception in noise from a source directly in front of the patient longitudinally. However, the UCI/seqBiCI group performed significantly worse over time compared to the simBiCI group for various speech perception in noise outcomes and localization abilities. Furthermore, the UCI/seqBiCI group performed significantly worse over time on quality of hearing and quality of life questionnaires. One year after receiving the second CI, the UCI/seqBiCI group performance did not statistically differ from the performance of the simBiCI group on all these outcomes. CONCLUSION: This randomized controlled trial on bilaterally severely hearing impaired participants found a significantly worse longitudinal performance of UCI/seqBiCI compared to simBiCI on multiple behavioral and self-reported outcomes regarding speech perception in noise and localization abilities. This difference is associated with the inferior performance of the UCI/seqBiCI participants during the years of unilateral CI use. After receiving the second CI however, the performance of the UCI/seqBiCI group did not significantly differ from the simBiCI group.